2014
DOI: 10.4187/respcare.03392
|View full text |Cite
|
Sign up to set email alerts
|

Prior Cardiac Surgery Is Independently Associated With Decreased Survival Following Infant Tracheostomy

Abstract: INTRODUCTION: Previous reports have demonstrated that prior cardiac surgery is independently associated with in-hospital mortality after infant tracheostomy. We aimed to determine whether these infants would continue to be at increased risk for death following hospital discharge. METHODS: A retrospective review was performed on subjects < 2 y of age who recovered from tracheostomy in the pediatric ICU at our institution between January 2007 and December 2011, with follow-up to December 2013. Survival to 1 y fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
53
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(62 citation statements)
references
References 17 publications
3
53
0
Order By: Relevance
“…[13] Additionally, in-hospital mortality of our cohort was also higher than reported in the majority of the available single center studies. [1,[3][4][5] This finding possibly reflects the inclusion of deaths that occur in patients discharged to chronic care or rehabilitation facilities. Indeed, in the study by Berry and colleagues, 19% of all patients who had tracheostomies had been discharged to a postacute care facility after at least one admission and 9.6% had only been discharged to such a facility.…”
Section: Commentmentioning
confidence: 99%
See 3 more Smart Citations
“…[13] Additionally, in-hospital mortality of our cohort was also higher than reported in the majority of the available single center studies. [1,[3][4][5] This finding possibly reflects the inclusion of deaths that occur in patients discharged to chronic care or rehabilitation facilities. Indeed, in the study by Berry and colleagues, 19% of all patients who had tracheostomies had been discharged to a postacute care facility after at least one admission and 9.6% had only been discharged to such a facility.…”
Section: Commentmentioning
confidence: 99%
“…Several institutions have reported their experiences with pediatric patients requiring tracheostomy following cardiac surgery. [1][2][3][4][5] The incidence of tracheostomy after pediatric cardiac surgery in these reviews ranged from 0.2-2.7%. Inhospital mortality was much more variable, ranging from 0-40% [1][2][3][4][5].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Current literature related to long‐term outcomes of children with tracheostomy placement and BPD shows mixed outcomes. While some studies report similar or even decreased rates of mortality in patients with BPD compared with other children with tracheostomy . others have found that BPD and prematurity are independent risk factors for mortality in children with tracheostomy …”
Section: Introductionmentioning
confidence: 99%